(untitled) (International Journal of Nursing Education, 2026)
Introduction: Evaluation and assessment is an important aspect for learning to assess the learner and provide feedback. This study aims to assess nursing students’ perceptions regarding Objective Structured Clinical Examination (OSCE) and Traditional Clinical Examination (TCE). Methods: A cross-sectional study was conducted using a total enumerative sampling technique with 122 Nursing students from the College of Nursing in Nagaland, India. A self-structured validated questionnaire, which had two sets of self-administered questionnaires on OSCE and TCE, with 15 questions, was administered to collect data on students’ perception towards OSCE and TCE. The participants rated their responses using a 5-point Likert scale, ranging from "strongly disagree" to "strongly agree," regarding the strengths and weaknesses of the practical methods employed. The students’ responses were analyzed using descriptive and inferential statistics. Results: The study revealed that out of 122 samples, 73.77% (90) had a good perception regarding OSCE, and only 26.22% (32) had an average perception. Concerning the Traditional Clinical (TCE) examination technique, 45.90% (56) had a good perception of TCE, and 54.09% (66) had an average perception. Many students found OSCE to be more organized, fair, and reliable, with minimal disturbance from patients during the examination, compared to TCE. There was a significant association between the perception of OSCE and TCE. Conclusion: Student nurses’ perception of practical and clinical assessment was found to prefer OSCE over TCE. Nurse educators can focus on using OSCE as an effective evaluation tool for students and further evaluate to improve the assessment method. However, students felt that a wide variety of clinical skills were also covered in TCE